Development of Numeracy Learning Videos to Improve Elementary Students’ Number Skills - Dewi, Yuli Ani Setyo; Choirudin, Choirudin (Edutechnium Journal of Educational Technology, 2025)
This study aimed to: (1) develop numeracy learning videos appropriate for elementary school students; (2) determine the validity of the numeracy learning videos based on assessments from material, media, and language experts; (3) assess the practicality and attractiveness of the videos from the perspectives of teachers and students; and (4) identify the effect of using the videos on students’ numeracy skills. The research employed a Research and Development (R&D) method using the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. The subjects were elementary school students, teachers, and expert validators. The instruments included validation sheets, teacher and student response questionnaires, and numeracy skill tests. The results showed that the developed numeracy learning videos were highly valid (average score ≥ 4.5 out of 5), practical, and engaging for students. There was also a significant improvement in students’ numeracy skills after using the videos. In conclusion, the developed numeracy learning video was feasible for use as an instructional medium in elementary schools and is recommended for broader implementation.